Influence of processing parameters on the hydrogen storage properties of dip coated lithium alanate thin films - Choosak Choawarot; Vilailuck Siriwongrungson; Janjira Hongrapipat; Shusheng Pang; Michael Messner (My University, 2021)
The complex metal hydride materials have been researched and reported as an effective hydrogen storage material with the gravimetric hydrogen storage capacity of around 5-7 wt%. In this paper, the 20 mg/cm 3 of lithium alanate solution prepared at 4 degree C and 25 degree C were dip coated on glass substrate. The post-annealing time was varied at 0 s, 1800 s and 3600 s. Phase and grain size were investigated using the X-ray powder diffraction. The hydrogen storage capacity and hydrogen desorption temperature were analyzed using thermogravimetric analysis. The lithium aluminium hydroxide hydrate and lithium hexahydroaluminate were observed on the deposited lithium alanate thin films when using the lithium alanate solution prepared at 4 degree C while only the lithium hexahydroaluminate was detected on the deposited lithium alanate thin films when the lithium alanate solution was prepared at 25 degree C. It was observed that the deposited lithium alanate thin films with lithium aluminium hydroxide hydrate have lower hydrogen storage capacity than the lithium alanate thin films without lithium aluminium hydroxide hydrate even the lithium alanate thin films with lithium aluminium hydroxide hydrate have smaller grain size. The hydrogen storage capacity and hydrogen desorption temperature of the deposited lithium alanate thin films were improved with longer annealing time.
Keywords: Hydrogen Storage and Materials; Hybrid Renewable Energy Systems; Environmental Engineering and Cultural Studies